Strongly Lifting Modules - Gareeb, Najmaddin H. (Sulaimani Journal for Pure and Applied Sciences, 2012)
In this paper we introduce the new concept of lifting modules, namely strongly lifting modules. Various properties and characterizations of strongly lifting modules are established and the relation between this type of module and some other known modules are discussed.